Analisis Respon Peserta Didik akan Kecanggihan Era Digital Terhadap Ragam Kearifan Lokal di Kabupaten Kuantan Singingi pada Kelas V SDN 05 Rambahan - Oni Oktika Sari (Mahaguru: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
The use of smartphones has now become a necessity for every level of society. In this era of increasingly sophisticated technology, everything is made quickly and very easily accessible via smartphone. Smartphones among students are more widely used as a means of entertainment and learning, especially to improve their mathematical knowledge. Many students think that mathematics is a scourge in learning activities at school. It cannot be denied that mathematics will always be related to our lives forever, as simple as counting. This research aims to analyze students' responses to the influence of smartphones on elementary school students' numeracy skills. The type of method in this research is qualitative research. The method used is descriptive-qualitative using instruments in the form of questionnaires. The data analysis technique in this research uses 4 Likert scale categories, namely (SS) strongly agree, (S) agree, (TS) disagree, (STS) strongly disagree. Each answer to the statement is grouped into 2 positive and negative responses. The Likert scale data obtained was then analyzed using Microsoft Excel. Based on the research results, 37 students in class VB at SDN 111 Pekanbaru were included in the good category regarding the influence of smartphones on elementary school students' numeracy skills. The categories obtained show that the influence of smartphones is not that bad in influencing elementary school students' numeracy skills.